PENGERTIAN TASAWUF DAN SEJARAH KEMUNCULANNYA - Azzahra Tharissa Zebua; Amira Shohwa Az-Zahra, Maftuh Ajmain (ADISAM PUBLISHER, 2025)
Sufism has many meanings, both in terms of language and terminology. However, in general, Sufism refers to simple behavior, staying away from worldly desires, and people who always worship and draw closer to Allah. Historically, a group of Orientalists thought that Sufism came from Christian sources. However, in Islam, the emergence of Sufism has occurred along with the growth and development of the Islamic religion itself, starting from the time of the Prophet Muhammad SAW and there are several phases, namely the first and second centuries of the Hijriyah, in the third and fourth centuries of the Hijriyah, in the fifth century of the Hijriyah, the sixth, seventh and eighth centuries of the Hijriyah and in the ninth, tenth centuries and after. In Indonesia, the development of Sufism can be said to have been influenced by Persia (Iran) and India. This article was written with the aim of understanding the meaning of Sufism, both in terms of language and terms put forward by experts, the history of the emergence of Sufism, and the development of Sufism in Indonesia. The method used in this article is the Literature Study Method or Literature Review